Opening doors with assistive technology. - Simpson, R.C (IEEE Engineering in medicine and biology magazine)
Results of the 2001 RESNA student scientific paper and student design competitions are presented. The topics dealt with included: scapula orientation in a virtual wheelchair push; repeatability of determining effective Young's modulus of buttocks soft tissue across multiple subjects; power and control system testing of five different types of power wheelchairs; modification of hybrid III test dummy for use in wheelchair studies; effect of adult-onset diabetes and/or peripheral neuropathy on acceleration threshold detection during horizontal translations; battery tester for people with physical and mental disabilities; design of a modular sensory feedback system to enhance physical education of persons with disabilities; an assistive technology key turning device for independent entryway access; ear-chin strap system for sleep apnea.